ANALISA POLA PEMESANAN PRODUK MODERN TRADE INDEPENDENT DENGAN MENEREPAKAN ALGORITMA FP. GROWTH (STUDI KASUS: PT. ADAM DANI LESTARI) - Russy Amelia; Dito Putro Utomo (STMIK Budi Darma, 2019)
Ordering in the field of sale and purchase of Ritail large and small ordinary happens to meet the needs of the store to reach consumers, it includes a list of goods and prices with different items and a variety of sizes, bookings made By looking at low or low stocks. Because the number of items that resulted in the booking is less efficient considering that each MTI store is tracking the different items, it is analyzed the pattern of the order based on the items simultaneously during the order by applying Algorithm. Growth, to easily order goods to be ordered and efficient. The results of the booking are at the same time by MTI, making it easier to order from the pattern analysis. Results obtained from the study of item recommendation is 2 or more items suggested through analysis using FP. Growth algorithm with confidence (confidence interval above 20%) and minimum 5% support. The Tools used Rapidminer 9.3 2019 generate tables and graphs from the FP. Growth algorithm and the Association Rule.Keywords: analysis, ordering products FP. Growth, RapidMiner 9.3.